Measurement of the leakage flux in the vicinity of a transformer core: Application to detection and localization of faults. Issue 2 (27th March 2020) - Duchesne, Stéphane; Morganti, Fabrice; Shulz, Carl; Roger, Daniel
Abstract : Purpose: This study presents a new method for the detection of faults in large transformer cores. It is based on the analysis of leakage flux components in the vicinity of the sheet stack. The purpose of this study is to provide a nondestructive analysis tool for transformer cores during the assembly process to detect accidental defects such as inter-laminar short circuits. Design/methodology/approach: The different components of the leakage flux allow localization of the fault in the stack and also permit to assess its severity. Out of the many kinds of defects which may appear in a transformer core, this method only detects those which actually cause an increase in the transformer's global iron losses, which are thus the most detrimental. Findings: The proposed method allows a more efficient control of the quality of the cores during their manufacturing process. Until now, it was only possible to know the quality of the core when the transformer was fully assembled. Research limitations/implications: The accuracy of the method depends on the size of the defect and may request many measurements to give usable information. Practical implications: Controlling iron losses in a core during its construction avoids heavy dismantling operations, both financially and temporally. Originality/value: This method can help transformer manufacturers optimize their building process. In addition, the method remains effective regardless of the size of the core considered.